Anastomotic leak management after a low anterior resection leading to recurrent abdominal compartment syndrome: a case report and review of the literature - Toutouzas, Kostas (BioMed Central, 2009)
INTRODUCTION: Low anterior resection is usually the procedure of choice for rectal cancer, but a series of complications often accompany this procedure. This case report describes successful management of an intricate anastomotic leak after a low anterior resection. CASE PRESENTATION: A 66-year-old Caucasian man was admitted to our hospital and diagnosed with a low rectal adenocarcinoma. He underwent a low anterior resection but subsequently developed fecal peritonitis due to an anastomotic leak. He was operated on again but developed abdominal compartment syndrome, multi-organ failure and sepsis. He was aggressively treated in the intensive care unit and in the operating room. Overall, the patient underwent four laparotomies and stayed in the intensive care unit for 75 days. He was discharged after 3 months of hospitalization. CONCLUSION: Abdominal compartment syndrome may present as a devastating complication of damage control laparotomy. Prompt recognition and goal-directed management are the cornerstones of treatment.